ANALISA POLA SPESIMEN PLASTIK UJI PUKUL CHARPY DENGAN MENGGUNAKAN PRINTER 3D - Etik Puspitasari (Universitas Lambung Mangkurat, 2019)
Impact testing is needed to measure the toughness of an object that requires a specimen as material to be requested. Where Impact testing specimens from metal that be moulded by casting cannot be made perfect because the angles of the notch are very difficult to make. For this reason, researchers try to make plastic specimens produced from 3D printers where notches or angles in the test specimens can be made precisely using a 3D printer. The design pattern of the plastic test specimen was made according to ASTM standard and tested using the Charpy test having a length of 73.6 mm, a width of 12.7 mm and a thickness of 10 mm, a notch shaped